Confiscation Of Assets For The Crime Corruption Used As Guarantee Mortgage - Tri Yatmoko (Corruptio, 2022)
Asset confiscation is one of the government's efforts to compensate for state losses. The Prosecutor's Office is one institution with the authority to carry out asset confiscation based on court decisions. In carrying out judicial decisions on corruption crimes, the Prosecutor's Office experiences various obstacles in practicing the value of justice, one of which is the seizure of assets attached to mortgages. The assessment of confiscating assets burdened with mortgages uses empirical juridical methods through library research and field research. The problem of this research focused on the practice of confiscating assets resulting from corruption in recovering state finances and how is the mechanism for confiscating assets resulting from corruption with mortgages attached. The study results show that in practice, the seizure of assets resulting from corrupt criminal acts takes a very long time because the time required for a case to obtain a binding court decision can take months, maybe even years. Next, the mechanism for confiscation of assets by prosecutors can confiscate assets resulting from corruption crimes that are pledged in the bank with mortgage rights attached, as long as the court can prove that the assets are indeed the result of corruption crimes and have permanent legal force (Eintracht). Because the criminal law position (public) is higher than civil law (private).